Epidemiology of Candida blood stream infections: experience of a tertiary care centre in North India - Chander, Jagdish; Singla, Nidhi; Sidhu, Shailpreet Kaur; Gombar, Satinder (The Journal of Infection in Developing Countries, 2013)
Introduction: Bloodstream infections due to Candida species are becoming a major cause of morbidity and mortality in hospitalized patients. The spectrum of candidemia has changed with the emergence of non-albicans Candida species, especially among critically ill patients. Methodology: In a retrospective study (July 2009 to December 2009) on candidemia, various Candida species isolated from blood cultures were characterized and studied along with the determination of their antifungal susceptibility to amphotericin B, itraconazole, and fluconazole by Etest. Probable risk factors for patients in the intensive care unit (ICU) presenting with candidemia were also analyzed. Results: During the study period, a total of 4651 samples were received, out of which 468 samples (10.06%) were positive for growth of organisms: 441 (94.20%) aerobic bacterial pathogens and 27 (5.79%) Candida species. The most common Candida spp. isolate was C. tropicalis (40.8%) followed by C. albicans (29.6%), C. glabrata (18.5%) and others (11.1%). Out of the 27 Candida strains, 24 (88.9%) were isolated from patients treated in the ICU. Among these, association of previous use of broad-spectrum antibiotics in 22 patients (91.6%) and central line catheter insertion in 20 patients (83.3%) were found to be statistically significant as compared to non-candidemia patients (p <0.05). Antifungal susceptibility testing of the isolates revealed a lower level of drug resistance to amphotericin B (18.5% of the isolates) versus 77.8% resistance to fluconazole. Conclusion: Rapid changes in the rate of infection, potential risk factors, and emergence of non-albicans Candida demand continued surveillance of this serious bloodstream fungal infection.